The Third Leap Zagreb Index for Trees - Jia-Ming Zhu; Nasrin Dehgardi; Xiaoxin Li (Journal of Chemistry)
The third leap Zagreb index is the sum of the products of vertex degrees and second degrees. In this paper, a lower bound on the third leap Zagreb index is established, and the extremal trees achieving this bound are characterized.